The moderating effect of women in boardrooms on the relationship between control of corruption and corporate sustainability performance - Tamer Elsheikh; Faozi A. Almaqtari; Hamood Mohammed Al-Hattami; Mohammed A. Al-Bukhrani; Abdou Ahmed Ettish (Discover Sustainability)
Abstract This paper examines the interplay between country-level control of corruption (CLCC), female board representation, and corporate sustainability performance using panel data analysis with fixed effect models on a global sample of over 36,000 observations from 2016 to 2021. Our analysis was conducted in four stages: first, assessing the baseline effects of gender diversity on sustainability outcomes within the context of corruption control; second, exploring these effects across groups categorized by Sustainable Development Goals (SDGs); third, examining differences between developing and developed regions; and finally, analyzing regional variations across America, Europe, and Asia. The results indicate that both control of corruption and increased board diversity have significant positive effects on environmental, social, and governance (ESG) scores, with a highly significant interaction effect, suggesting a substantial combined influence. Additionally, analyses based on SDG alignment demonstrate that control of corruption improves ESG performance irrespective of SDG level, while board diversity benefits both high and low SDG groups. Regional analyses further reveal varied effects across America, Europe, and Asia. These findings underscore the significance of corruption control and female representation in enhancing corporate sustainability worldwide, emphasizing the potential for firms to improve ESG performance by prioritizing anti-corruption efforts and promoting board diversity. This international study contributes valuable insights into the relationship between country-level governance, corporate board composition, and sustainability outcomes across diverse contexts, highlighting the importance of tailoring sustainability policies and practices based on regional and developmental nuances.